Tax Audit Effectiveness and Tax Compliance Behaviour in Benin City, Edo State, Nigeria - Wilson-Oshilim, Uduak; Omonhinmin, Esele (NIU Journal of Management Sciences, 2026)
This empirical work examines the effect of tax audit effectiveness on tax compliance in Benin City, Edo State, Nigeria. Specifically, it evaluates the influence of audit frequency, audit quality, and penalty enforcement on compliance behaviour, while controlling for taxpayer education. A descriptive survey research design was utilised, while 384 respondents were sampled in the study. The structured questionnaire served as a means of collecting data which was analysed with the aid of descriptive statistics, correlation analysis, and multiple regression techniques. The outcomes demonstrate that audit frequency, audit quality, and penalty enforcement each exert a significant positive effect on tax compliance. Taxpayer literacy also shows a positive influence, indicating that informed taxpayers are more likely to comply voluntarily with tax obligations. These results are consistent with the Economic Deterrence Theory, which emphasises the role of detection probability and enforcement severity in shaping compliance behaviour, while also supporting complementary perspectives that highlight the importance of fairness and awareness in tax administration. The study concludes that although deterrence mechanisms are effective in promoting compliance, their impact is strengthened when implemented with transparency, fairness, and adequate taxpayer education. It therefore recommends the expansion of taxpayer education programmes, improvement in audit professionalism and transparency, and consistent enforcement of penalties to enhance compliance and build trust in the tax system. Finally, this research recommends that subsequent study should be empirically executed on the informal sector, undertake longitudinal analyses of compliance behaviour, and conduct comparative studies across different regions in Nigeria. Keywords: Audit, Tax Compliance, Audit Frequency, Penalty Enforcement, Audit Quality.